2021
DOI: 10.21037/tau-20-994
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific mortality of low and selective intermediate-risk prostate cancer patients with active surveillance or watchful waiting

Abstract: Background: Active surveillance or watchful waiting (AS/WW) is increasingly being used as an alternative strategy to radical prostatectomy or radiation therapy for appropriately selected patients with prostate cancer (PCa). However, the prognosis of low-risk and selective intermediate-risk PCa patients after AS/WW is poorly defined. In this study we reviewed the patients registered in the Surveillance, Epidemiology, and End Results (SEER) Program to establish a competing risk nomogram for the prediction of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…Of the 3,322 patients enrolled in our study, 16.28% of people died of spPCa. Compared with patients with only primary PCa, Wu et al (12) found that only 1.17% patients died of primary PCa, which was much lower than the proportion of PCa deaths (1.17% vs. 16.28%) in our study. In addition, compared with the mortality rate of primary prostate cancer (7.3%) by the International Agency for Research on Cancer estimates, the mortality rate of spPCa patients was significantly worse than that of primary prostate cancer patients.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Of the 3,322 patients enrolled in our study, 16.28% of people died of spPCa. Compared with patients with only primary PCa, Wu et al (12) found that only 1.17% patients died of primary PCa, which was much lower than the proportion of PCa deaths (1.17% vs. 16.28%) in our study. In addition, compared with the mortality rate of primary prostate cancer (7.3%) by the International Agency for Research on Cancer estimates, the mortality rate of spPCa patients was significantly worse than that of primary prostate cancer patients.…”
Section: Discussioncontrasting
confidence: 86%
“…The treatments of PCa mainly include waiting for active surveillance or watchful waiting (AS/WW), radical prostatectomy, and radical radiotherapy. Generally speaking, the main indications of AS/WW include T1–2, Gleason < 8, low tumor load at biopsy, life expectancy > 10 years, age > 70–75 years, and PSA lower than 10 ng/ml ( 12 ). However, a prospective study in the United States pointed out that active monitoring of low-risk PCa might cause patients to miss the best time for treatment, reducing their survival expectations ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have investigated this relationship, but results of other population-based analyses lead to speculation that rising PSA is also associated with other-cause mortality. 8,9,19–22 The explanation for this relationship is unclear, but there are several potential explanations. The most plausible explanation is a referral artifact: there is a lower propensity to PSA testing and taking of a biopsy in men who have comorbidities; such men are only likely to undergo a PSA test or biopsy if they represent themselves with clear clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This poses a potential challenge for drawing inferences from large multi-institutional databases that include institutions using different grading schemes if those institutions do not report the grading methodology used or the fractions of Gleason patterns present in a given RP. 25,26 Outcomes in Each Grade Group (GG) With Individual Tumor Nodule (TN) and Corresponding Global Grading Highest-Grade TN GG Highest-Grade TN Gleason Score Global GG Global Gleason Score…”
Section: Discussionmentioning
confidence: 99%